REVITALISASI TATA KELOLA PENDIDIKAN MELALUI IMPLEMENTASI MANAJEMEN BERBASIS SEKOLAH DI SEKOLAH DASAR - Chindytia; Agung Gede Agung , Anak; Putu Angelina Venia Putri Tama; Komang Ristia Dewi, Ni; Koming Devy Masyani, Ni (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aimed to examine the revitalization of educational governance through the implementation of School-Based Management (SBM) at SD Negeri 6 Sudimara. The study employed a descriptive qualitative approach with a case study design. The research subjects consisted of 1 principal and 6 teachers who were directly involved in school management. Data were collected through questionnaires, interviews, observations, and documentation. The research instruments were declared valid based on Gregory validity testing and Pearson Product Moment correlation, and reliable with a Cronbach’s Alpha coefficient of 0.85. The results showed that the implementation of SBM at SD Negeri 6 Sudimara was categorized as good to very good. The percentage results for each component were curriculum management at 92% (very good), management of educators and educational staff at 88% (good), student management at 84% (good), facilities and infrastructure management at 84% (good), public relations management at 90% (very good), excellent service management at 86% (good), and financial management at 94% (very good). The SWOT analysis revealed that the school’s strengths were democratic principal leadership, good stakeholder relationships, and transparent financial management. However, the school still faced challenges related to limited facilities, infrastructure, and school funding. Therefore, adaptive development strategies are needed through optimizing school resources, strengthening cooperation with the community, and improving teacher professionalism to support sustainable educational quality improvement. Keywords: School-Based Management, Educational Governance, SWOT Analysis